Effect of multimodality treatment on overall survival for patients with metastatic or recurrent HPV‐positive head and neck squamous cell carcinoma. Issue 5 (30th April 2014) - Deeken, John F.; Newkirk, Kenneth; Harter, K. William; Marshall, M. Blair; Banovac, Filip; Johnson, Lynt; Wang, Hongkun; Wang, Yiru; Zhuang, Tingting; Jay, Ann K.; Berkowitz, Frank; Esposito, Giuseppe; et al.
Abstract: Background: The optimal treatment for patients with recurrent human papillomavirus (HPV)‐positive head and neck cancer is poorly understood. Methods: We investigated treatments and outcomes in patients with recurrent head and neck cancer. Treatments included salvage neck surgery, metastasectomy, hypofractionated reirradiation, chemoembolization, and chemotherapy. Treatment outcomes were compared based on HPV status. Results: A total of 37 patients were identified (12 HPV positive and 25 HPV negative). Demographics were similar. Overall, there was a trend toward a higher number of total treatment interventions in patients with HPV‐positive disease (4.5 vs 2.6), but this was statistically insignificant ( p = .066). After a mean follow‐up of 21 months, median survival in HPV‐negative patients was 10.6 months, whereas the median survival had not been reached for HPV‐positive patients. Of the 12 HPV‐positive patients, 7 were still alive (58%) after a mean follow‐up period of 33 months. Conclusion: Multimodality aggressive therapy may improve overall survival in patients with recurrent HPV‐positive disease. Further prospective research is warranted. © 2014 Wiley Periodicals, Inc. Head Neck 37: 630–635, 2015